A Centennial Episode of Weak East Asian Summer Monsoon in the Midst of the Medieval Warming. Issue 9 (28th September 2018) - Jin, Chunhan; Liu, Jian; Wang, Bin; Wang, Zhiyuan; Yan, Mi
Abstract: Recent paleoproxy evidence has suggested that there is a centennial episode of weaker East Asian summer monsoon (EASM) within the Medieval Warm Period, in which the EASM is generally strong. This study aims to explore the causes of this phenomenon and determine what controls the centennial variability of the EASM. With the Community Earth System Model, a suite of control and forced experiments were conducted for the past 2, 000 years. The model simulates a warm period over EA (East Asia) from CE 801–1250 with a generally increased summer mean precipitation over the northern EA; however, during CE 980–1100, the EASM is significantly weaker. On the multi‐decadal to centennial time scale, a strong EASM is associated with a La Niña‐like Indo‐Pacific warming, and a weak EASM with the El Niño‐like conditions. This sea surface temperature anomaly pattern represents the leading EOF (empirical orthogonal function) mode of centennial sea surface temperature variations, which are primarily forced by solar radiation and volcanic activity. In contrast, land use/land cover and greenhouse gases as well as internal dynamics play a negligible role. The weak EASM during CE 980–1100 is attributed to the relatively low solar radiation, which leads to a prevailing El Niño‐like Indo‐Pacific cooling with the strongest cooling occurring in the equatorial western Pacific. The suppressed convection over the equatorial western Pacific directly induces a Philippine Sea anticyclone anomaly, which increases the southern China precipitation, while suppressing Philippine Sea precipitation. The latter excites a meridional teleconnection that induces anomalous northerly winds and dry conditions over northern China. Key Points: Proxy data and model results suggest that there is a centennial episode of weaker East Asian summer monsoon during the Medieval Warm Period On the multidecadal to centennial time scale, a strong East Asian summer monsoon is associated with a La Nina‐like Indo‐Pacific warming The weakening of the East Asian summer monsoon during the CE 980‐1100 is mainly attributed to the relatively low solar radiation